1984
DOI: 10.1083/jcb.98.2.629
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of protein transport across lymphatic endothelium in vitro.

Abstract: The purpose of the work was to develop an in vitro model for the study of lymphatic endothelium and to determine, using this model, whether or not a cytoplasmic process may be involved in transendothelial transport . Segments of canine renal hilar lymphatics were dissected clean, cannulated at both ends, and transferred to a perfusion chamber for measurement of transendothelial protein transport and for ultrastructural tracer studies . The segments were subsequently processed for light and electron microscopy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…They interpreted this as evidence of a specialization of the plasmalemmal vesicles in the pulmonary microcirculation. It has also been shown that at 4°C the transport of CF is less than at higher, more physiological temperatures of mammals (O'Morchoe et al 1984). We found that normal seasonal changes in the ambient water temperature did not alter either the lack of binding of CF to the endothelial cell surface or the movement of CF or native ferritin through endothelial vesicles.…”
Section: Discussionsupporting
confidence: 48%
“…They interpreted this as evidence of a specialization of the plasmalemmal vesicles in the pulmonary microcirculation. It has also been shown that at 4°C the transport of CF is less than at higher, more physiological temperatures of mammals (O'Morchoe et al 1984). We found that normal seasonal changes in the ambient water temperature did not alter either the lack of binding of CF to the endothelial cell surface or the movement of CF or native ferritin through endothelial vesicles.…”
Section: Discussionsupporting
confidence: 48%
“…Overall heat or massage leads to increased blood and/or lymph flow that results in higher uptake of SC or intramuscularly administered drugs. In addition, changes in temperature affected transport of proteins in dog lymphatics (61). The transport rate of proteins was reduced by up to 49% when temperature was reduced to 4°C from 37°C, and the transport rate was increased by 48% when temperature was raised to 40°C.…”
Section: Physiological or Other Factors Influencing The Lymphatic Uptakementioning
confidence: 92%
“…40 Transfer of various tracers such as ferritin and horseradish peroxidase also occurs across the lymphatic endothelium in association with cytoplasmic vesicles. 38,[41][42][43] The driving force for fluid transfer from the interstitium into the initial lymphatics has been the subject of significant debate. Clearly, a potential energy difference in the fluid phase between the interstitium and the lymphatics is required and may take the form of a chemical gradient, with the associated osmotic or oncotic pressure gradients, or a hydrostatic pressure differential.…”
Section: Lymphatic Drainage Of the Interstitial Spacementioning
confidence: 99%